Prognosis and management in the first few days after a transient ischemic attack or minor ischaemic stroke. - Giles, M; Rothwell, P (2006)
The risk of recurrent stroke during the first few days after a transient ischaemic attack (TIA) or minor stroke is very much higher than previously estimated. However, there is considerable international variation in how patients with suspected TIA or minor stroke are managed in the acute phase, some healthcare systems providing immediate emergency inpatient care and others providing non-emergency outpatient clinic assessment. This review considers what is known about the early prognosis after TIA and minor ischaemic stroke, what factors identify individuals at particularly high early risk of stroke, and what evidence there is that urgent preventive treatment is likely to be effective in reducing the early risk of stroke.